Memeriksa Striae Gravidarum untuk Memperkirakan Laserasi Perineum - Khrisnamurti, Sinta; Nurdiati, Detty Siti; Setiyarini, Wahyu Ikka (JURNAL KESEHATAN REPRODUKSI, 2018)
Background: Striae gravidarum is a common phenomenon that occurs in pregnant women and a marker of decrease in skin elasticity. Poor elasticity of the perineum can result perineal laceration in vaginal childbirth. This study was to determine the relationship of striae gravidarum perinenum with the occurrence lacerations in normal labor, and the factors that most influence the occurrence of mild and severe perineal lacerations.Method: Used a cross sectional design, with a sample of 188 respondents. Assessment striae gravidarum using Atwal et al (2006) which has been modified, assessment of perineal lacerations used RCOG (2006). Data collection was done during the months of April to July 2015 in the maternity room Panembahan Senopati Bantul Hospital.Results: Factors that influence the occurrence of mild laceration were striae gravidarum moderate-severe (RP 1,230: CI 95% 1,23053-1,23066), primiparous (RP 1,2675: CI 95% 1,13709-1,41298). Factors that influence the occurrence of severe laceration were striae gravidarum moderate-severe (RP 1,676: CI 95% 1,246-2,255), primiparous (RP 1,117: CI 95% 1,1172-1,1175), the lithotomy position (RP 1,012: CI 95% 1,011-1,0629).Conclusion: Striae gravidarum is factor that influence the occurance of perineal laceration. Checking of striae gravidarum can be to estimate the severity of perineal laceration, the more scores striae gravidarum more severe perineal laceration that may be experienced by childbirth mothers.Â Keywords: striae gravidarum; perineal laceration; childbirth